Association between oxidative balance score and osteosarcopenia in US adults: insights from a population-based study - Sun, Zhonghua; Yang, Jiahui; Tao, Xinyu; Weng, Yangyang; Ding, Ling; Xu, Yameng; Qu, Chen; Liu, Zhengxia (Frontiers in Nutrition, 2025)
BackgroundSarcopenia and osteoporosis are interrelated conditions that significantly contribute to adverse health outcomes. Both conditions are negatively influenced by oxidative stress. While antioxidant supplementation has been explored as a potential intervention, its efficacy remains inconsistent, highlighting the complexity of oxidative stress management. The oxidative balance score (OBS) is a novel metric that evaluates the interplay between pro-oxidants and antioxidants, providing a holistic assessment of the body’s oxidative status. Despite its promise, the relationship between OBS and osteosarcopenia—a coexistence of sarcopenia and osteoporosis—has not been extensively studied.MethodsData from the National Health and Nutrition Examination Survey, a national cross-sectional study. The association between OBS and osteosarcopenia was evaluated using weighted logistic regression, restricted cubic spline, and receiver operating characteristic curve analyses. Subgroup analyses were conducted to explore potential population differences. Additionally, we examined the relationships between dietary and lifestyle OBS and osteosarcopenia separately.ResultsThe study included 3,336 adults (mean age: 43.30 ± 13.73 years; 53.15% males) with complete data on muscle mass and bone mineral density. OBS was linearly and negatively associated with osteosarcopenia and effectively differentiated individuals with osteosarcopenia from healthy individuals. No significant interactions were observed in the subgroup analyses. Lifestyle OBS showed a stronger association with osteosarcopenia compared to dietary OBS.ConclusionOBS is inversely associated with the prevalence of osteosarcopenia, indicating that individuals with higher OBS tend to have a lower likelihood of osteosarcopenia. Moreover, OBS demonstrates good discriminative ability, effectively identifying individuals who are more likely to have osteosarcopenia from healthy individuals.